Stabilizing coherence with nested environments: a numerical study using kicked Ising models. (4th July 2016) - González-Gutiérrez, C; Villaseñor, E; Pineda, C; Seligman, T H
Abstract: We study a tripartite system of coupled spins, where a first set of one or two spins is our central system which is coupled to another set considered, the near environment, in turn coupled to the third set, the far environment. The dynamics considered are those of a generalized kicked spin chain in the regime of quantum chaotic dynamics. This allows us to test recent results that suggest that the presence of a far environment, coupled to the near environment, slows decoherence of the central system. After an extensive numerical study, we confirm previous results for extreme values and special cases. In particular, under a wide variety of circumstances an increasing coupling between near and far environment, slows decoherence, as measured by purity, and protects internal entanglement.